Influence of Load Parameters on Efficiency of Transformer Replacement in Distribution Networks - N. S. Petrashevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a step-by-step optimization method for transformer replacement of the 6–10 kV power distribution networks on the basis of sensitivity theory. The influence of load parameters on the efficiency of transformer replacement in distribution networks has been evaluated in the paper. The paper reveals that the first step of optimization is the most effective one and it is particularly important in the case of the limited financial resources.